Strategi Politik Partai Psi Di Era Digital Dalam Meningkatkan Partisipasi Pemilih Muda - Nabila Kheisya Zalvadhia; Silvia Nuraeni; Bunga Indriani Azzahra; Caritas Nadya Anisti; Kezia Marlinata Sinaga; Restu Rahmawati (CV. ITTC INDONESIA, 2025)
PSI uses the digital era to increase the political participation of young voters. With a significant population of young voters inIndonesia, digital strategies have become key to reaching and influencing the political preferences of the millennial and Gen Z generations. This case study method employs a qualitative approach. The research results show that PSI uses progressive digital strategies through platforms such as Instagram, Twitter,and YouTube. They communicate in a relaxed,inclusive manner and are responsive to social issues relevant to young people. Although there are issues with narrative consistency and reach limitations, this strategy has successfully increased engagement and shaped the party's image as modern and close to the aspirations of the younger generation. To enhance the effectiveness of future digital campaigns, this research suggests the use of data analytics and better audience segmentation.